(untitled) (Research, Society and Development, 2021)
The study aimed to identify the social and assistance barriers in the daily lives of HIV positive women. This was an integrative literature review using a sample of 18 original articles from the last 5 years, selected from the following databases: Virtual Health Library (VHL), Latin American and Caribbean Literature on Health Sciences (LILACS) , Electronic Library Scientific Library Online (SCIELO), which can be found in synoptic tables according to the study categories. The results showed sadness, anguish, prejudice, changes in family and social relationships, concealment of the diagnosis and lack of adherence to treatment. It was found that the confirmation of HIV has a great impact on women’s lives and that a holistic care is needed to deal with seropositivity. This study can contribute to future research aimed at improving multidisciplinary care and quality of life for HIV carriers. Thus, idealizing an improvement in the quality of life of seropositive women, in multidisciplinary, broader, more qualified care, reducing care and social barriers.